Influence of a coach development curriculum on preservice coaches' habitus - Kuklick, C.; Harvey, S.; King, R. (International Sport Coaching Journal, 2023)
The purpose of this cross-sectional study was to analyze the influences of a 4-year university-based coach development curriculum on coaching-students` habitus. The occupational socialization framework and Bourdieu`s theory of practice were used to capture the socialization factors that influence how coaching habitus remain continuous or are modified across the temporal phases of coaching-students` socialization (i.e., acculturation and preservice professionalization). Data were collected through interviews, interview reflections, and coaching philosophies, which were analyzed and compared across entering (ENCS; n = 23) and exiting (XCS; n = 10) cohorts. Habitus formation, enacting coaching habitus, and influences on coaching habitus were the main themes. XCS differed from ENCS by utilizing individualized instructional coaching, planning and programming, various methods of coaching, and reflection and lifelong learning as key strategies to enact their habitus, which showed the influence of preservice professionalization on gaining cultural capital in the coaching field. The findings provide support for how practicum cites, course content, and coach developers within the curriculum influenced coaching-students` habitus. This research offers novel insights in regard to the approaches used in the curriculum, the integration of occupational socialization and Bourdieu`s theory of practice frameworks, and the cross-comparative design for analyzing programmatic effectiveness.